Mengapa Harus Iklan ? - Situmorang, James R. (Business Administration Study Program - Universitas Katolik Parahyangan, 2008)
Advertising is one of promotion tools besides sales promotion, public relations (PR), personal selling and direct marketing. Advertising is still favourite for producers to promote their product. Advertising is anywhere around us, especially in big city so we always see advertising every day. Even advertising through village people including mountain and forest areas by television channel. This article will try to discuss 5 main decisions in advertising. First is Mission: What are the advertising objectives? Second, Money: How much can be spent Third, Message: What message should be sent? Fourth, Media: What media should be used? Fifth, Measurement: How should the results be evaluated? Keywords: Advertising, promotion, message, budget, media, television, communicative